A Guide to Sustainable Corporate Responsibility From Theory to Action - Ditlev-Simonsen, Caroline D. (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book discusses the challenges and opportunities faced by companies in an age that increasingly values sustainability and demands corporate responsibility. Beginning with the historical development of corporate responsibility, this book moves from academic theory to practical application. It points to ways in which companies can successfully manage their transition to a more responsible, sustainable way of doing business, common mistakes to avoid and how the UN Sustainable Development Goals are integral to any sustainability transformation. Practical cases illustrate key points. Drawing on thirty years of sustainability research and extensive corporate experience, the author provides tools such as a Step-by-Step strategic guide on integrating sustainability in collaboration with stakeholders including employees, customers, suppliers and investors. The book is particularly relevant for SMEs and companies operating in emerging markets. From a broader perspective, the value of externalities, full cost pricing, alternative economic theories and circular economy are also addressed. .